1997
DOI: 10.1007/bf02832666
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of male recovering substance abusers living in a self-help, self-governed setting

Abstract: Adult men (n = 132; 92% of the population) with histories of alcohol/drug use disorders were interviewed upon their entry to 11 Oxford Houses located in the state of Illinois. Individuals still in residence at a six-month follow-up (n = 48) were reinterviewed; prior to the follow-up interview, 42 men had left voluntarily and 42 men had been evicted for abuse or disruptive behavior. The men remaining in residence tended to be older (M age = 37 years), were disproportionately African American (56%), and were les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…From a practical perspective, Oxford Houses tend to be in neighborhoods where there is low drug-trafficking and criminal activity (Jason et al, 2001; Ferrari, Jason, Blake, Davis, & Olson, 2006), thereby reducing opportunities to become involved in illegal activities. Additionally, most Oxford House residents are able to maintain stable employment and an adequate income (Jason et al, 1997). In fact, Jason et al (2006) found that Oxford House residents had a significantly higher monthly income at a two-year follow-up than individuals who received standard substance abuse treatment.…”
Section: Discussionmentioning
confidence: 99%
“…From a practical perspective, Oxford Houses tend to be in neighborhoods where there is low drug-trafficking and criminal activity (Jason et al, 2001; Ferrari, Jason, Blake, Davis, & Olson, 2006), thereby reducing opportunities to become involved in illegal activities. Additionally, most Oxford House residents are able to maintain stable employment and an adequate income (Jason et al, 1997). In fact, Jason et al (2006) found that Oxford House residents had a significantly higher monthly income at a two-year follow-up than individuals who received standard substance abuse treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One such option is Oxford House (see Jason et al, 1997), a mutual-help residence that began as a home for substance abuse recovery and grew to over 850 houses in the United States, including homes for women and women with children . Oxford Houses are completely self-run by residents.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Research on Oxford House participants indicated that a primary reason individuals chose to become members was the camaraderie and abstinence social support they received within the setting (Jason, Ferrari, Smith, et al, 1997; Ferrari, Jason, Olson, Davis & Alvarez, 2002). Although both female and male residents reported valuing social support in recovery, women placed greater emphasis on social supports than did men (Kim, Davis, Jason, & Ferrari, 2006).…”
mentioning
confidence: 99%
“…One area that has only begun to be explored in Oxford House is the extent to which the interpersonal dynamics of a household have on an individual’s experience of his or her house. Given that social support is reported as one of the driving motivations for persons entering Oxford House, advancing knowledge regarding correlates of PSOC is warranted (Jason, Ferrari, Smith, et al, 1997). …”
mentioning
confidence: 99%